(untitled) (Bangladesh Journal of Medical Science, 2019)
Objectives: The main aim of this study was to determine the level of knowledge about rheumatoid arthritis disease among patients presenting with arthralgia in a tertiary care teaching hospital, Pakistan. Materials and Methods: A cross-sectional study during the period of September 2015 - March 2016 in the Medical Out-Patient Department, Shaheed Mohtarma Benzir Bhutto Medical University Hospital, a tertiary care teaching hospital in Larkana, Pakistan. Patients above 40 years of age of either gender were included in the study. A non-probability purposive sampling technique was employed to include the participants in the study. A pre-designed questionnaire with open and close ended questions was used. The questionnaire in English language was also translated in local language to facilitate the participants. All the statistical analysis was conducted using Stata statistical software 14. Results: A total number of 251 participants completed the questionnaires. 42 (56.6%) were from rural settings, while 233 (92.8%) were females. The overall mean age was 59 ± 8.69 years. There were 139 (55.4%) of the participants were ≥ 60 years of age. The average BMI was 23.1 ± 4.3. Moreover, 144 (57.4%) participants were found noneducated. The duration of the disease was less than 10 years in 154 (61.4%) of the participants. While, 157 (62.5%) participants were not knowing about factors which contribute to the onset of rheumatoid arthritis. We observed that, on the basis of responses to the relevant questions, only 4 (1.6%) participants were considered fully aware. Conclusion: We observed lack of knowledge in majority of the participants presenting with arthralgia. The public awareness and education through different vertical programs as well as through social media in the country which can play very important role. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.808-813